THE DEVELOPMENT OF GUIDELINES FOR ACADEMIC ADMINISTRATION BASED ON GOOD GOVERNANCE PRINCIPLES FOR SECONDARY SCHOOL UNDER THE OFFICE OF THE SECONDARY EDUCATION SERVICE AREA LOEI, NONG BUA LAMPHU - Tiamduangkhae, Chonmapat; Chittranun, Thatchai (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
The purpose of this research was 1) To study the current conditions. The desirable conditions and needs of the academic administration based on good governance of schools under Loei & Nong bua lamphu secondary educational service Area Office. 2) To develop guidelines for implementation of academic administration based on good governance of schools under Loei & Nong Bua Lamphu secondary educational service Area Office. By using a questionnaire to collect data from a sample group of 324 administrators and teachers with 5 experts. The research instruments were questionnaires, interviews and assessments. The statistic used for the data analysis were percentage, mean and standard deviation. The results of the research were as follows: 1) Current conditions, desirable conditions, and prioritization of the needs of the academic administration based on good governance of schools under Loei & Nong bua lamphu secondary educational service Area Office. Overall current condition was at the high level. The highest mean is evaluation. Overall desirable condition was highest level. The highest mean is education supervision. The order of needs, the aspect with the most need is the school curriculum development and educational supervision. 2) Guidelines for the operation of the academic administration based on good governance of schools under Loei & Nong Bua Lamphu secondary educational service Area Office, consists of 6 elements, 30 approaches, namely 1) Educational curriculum development 5 approaches 2) teaching and learning management in educational institutions 5 approaches 3) development of the learning process 5 approaches 4) evaluation 5 approaches 5) education supervision 5 approaches 6) development and use of technology for education 5 approaches. The results of assessing the feasibility of the academic administration based on good governance of schools under Loei & Nong Bua Lamphu secondary educational service Area Office. Found that: The guidelines are appropriate and there is at the most level of overall appropriate. At the highest level, the same of all items. The aspect that is most appropriate is the aspect of educational curriculum development, educational supervision, and teaching & learning management in educational institutions. When considering each item, it was found that it was most likely the same for all items. The most likely aspect is student screening.